Experiment on Radiant Floor Heating System of Air-source Heat Pump in Hotan Area - Sun Zhili; Ren Tong; Liu Qiyou; Jiao Feng; Li Jintao; Liang Di; Wang Yi'an (Zhileng xuebao)
Heat pump heating can solve the environmental pollution problems caused by coal heating. This study used an air source heat pump system applied in Hotan area as the research object and tested the in-situ performance of the air source heat pump heating system with the radiant floor within 24 h on a typical day (the ambient temperature was -4.7–9.6 ℃ while the RH was 26%–61%). The results show that the highest COP of the heat pump heating system is 2.64 at around 16:00, and the lowest value is 1.98 at around 08:00. Owing to the relatively good insulation performance of the building, when the outdoor temperature changes, the room temperature fluctuates slightly; the room temperature can be stable between 23–24 °C all day, and the room temperature can be above 20 ℃ even for northern rooms. The air source heat pump heating system using radiant floor heating can satisfy the heating demand of the Hotan area. The system has high efficiency and broad application potential.